2007
DOI: 10.1007/s10750-006-0569-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of nitrate uptake by New Zealand marine macroalgae and evidence for two nitrate transporters in Ulva intestinalis L.

Abstract: Kinetic constants were determined for nitrate uptake in three species, Pterocladiella capillacea (S.G. Gmelin) Santelices et Hommersand (Rhodophyceae, Gelidiales), Ulva intestinalis L. (Chlorophyceae, Ulvales) and Xiphophora chondrophylla (Turner) Montagne ex Harvey (Phaeophyceae, Fucales), of New Zealand macroalgae, with K m values ranging from 10 to 17 lM and V max values from 3 to 65 lmole g -1 dry weight h -1 . There was no effect of ammonium on nitrate uptake by Pterocladiella capillacea or Xiphophora cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
9
0
4
Order By: Relevance
“…As a fast-growing, ephemeral species, Ulva has a higher nitrogen demand to reach maximum growth compared to Fucus, a slow growing species (Pederson and Borum, 1997 Ulva exhibits an ability to uptake in NH 4 + as an immediate surge, but ultimately, longer exposure to high levels of NH 4 + result in reduce uptake (Pederson and Borum, 1997). Rees et al (2007) showed significantly increased uptake rates of NH 4 + in Ulva intestinalis when NH 4 + concentrations increased, these uptake rates exceed those for NO 3 -, and the increased uptake of NH 4 + came with reduced uptake of NO 3 -. Fucus becomes saturated at NH 4 + and NO 3 -concentrations around 10-30 µM and the maximum uptake rates in this species are less than half of those observed in Ulva (Pederson and Borum, 1997).…”
Section: Algal Growthmentioning
confidence: 99%
“…As a fast-growing, ephemeral species, Ulva has a higher nitrogen demand to reach maximum growth compared to Fucus, a slow growing species (Pederson and Borum, 1997 Ulva exhibits an ability to uptake in NH 4 + as an immediate surge, but ultimately, longer exposure to high levels of NH 4 + result in reduce uptake (Pederson and Borum, 1997). Rees et al (2007) showed significantly increased uptake rates of NH 4 + in Ulva intestinalis when NH 4 + concentrations increased, these uptake rates exceed those for NO 3 -, and the increased uptake of NH 4 + came with reduced uptake of NO 3 -. Fucus becomes saturated at NH 4 + and NO 3 -concentrations around 10-30 µM and the maximum uptake rates in this species are less than half of those observed in Ulva (Pederson and Borum, 1997).…”
Section: Algal Growthmentioning
confidence: 99%
“…Em plantas vasculares, foram identificados três sistemas de transporte de nitrato, com base em suas propriedades cinéticas: i) constitutivo com alta afinidade (K m = 6-20 µM), ii) induzível com alta afinidade (K m = 20-100 µM) e iii) induzível com baixa afinidade (ativo em concentrações de nitrato superiores a 500 µM) (Crawford & Glass, 1998;Glass, 2003). Segundo Rees et al (2007), as propriedades cinéticas de captação de nitrato em macroalgas sugerem a existência de sistemas de alta afinidade. Além disso, o efeito do amônio sobre a captação de nitrato por Ulva intestinalis indicaria a presença de pelo menos dois sistemas: i) sensível a amônio e, possivelmente, regulado por este íon e ii) insensível a amônio (Rees et al, 2007).…”
Section: Metabolismo Do Nitratounclassified
“…Segundo Rees et al (2007), as propriedades cinéticas de captação de nitrato em macroalgas sugerem a existência de sistemas de alta afinidade. Além disso, o efeito do amônio sobre a captação de nitrato por Ulva intestinalis indicaria a presença de pelo menos dois sistemas: i) sensível a amônio e, possivelmente, regulado por este íon e ii) insensível a amônio (Rees et al, 2007). Os autores afirmam também que as concentrações usadas na determinação das constantes cinéticas de captação de nitrato por macroalgas não são suficientemente altas para estabelecer a existência de um sistema de baixa afinidade (Rees et al, 2007 (Crawford, 1995;Tischner, 2000;Taiz & Zeiger, 2004;Suzuky & Knaff, 2005).…”
Section: Metabolismo Do Nitratounclassified
See 2 more Smart Citations